Blockchain technology in the energy industry: terminology, technical foundations, implications and application potentials - Heck, Thorsten (2019)
Fil: Heck, Thorsten. University of Applied Sciences Hochschule Kaiserslautern. Faculty of Business Administration; Alemania.